2023
DOI: 10.1002/jat.4522
|View full text |Cite
|
Sign up to set email alerts
|

Biological mechanism of ZnO nanomaterials

Abstract: Modern nanotechnology has made zinc oxide nanomaterials (ZnO NMts) multifunctional, stable, and low cost, enabling them to be widely used in commercial and biomedical fields. With its wide application, the risk of human direct contact and their release into the environment also increases. This review aims to summarize the toxicity studies of ZnO NMts in vivo, including neurotoxicity, inhalation toxicity, and reproductive toxicity. The antibacterial and antiviral mechanisms of ZnO NMts in vitro and the toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…In our research, we have demonstrated the application of ZnO NPs on bacteria (Figure 1A) and viruses (Figure 1B). 55 Numerous studies have reported the beneficial use of ZnO NPs in cancer treatment. For instance, it has been found that black mulberry loaded MN-ZnO NPs induce apoptosis in gastric cancer cells (AGS) by enhancing the formation of ROS, reducing mitochondrial membrane potential (MMP), evaluating apoptotic morphological changes using AO/EtBr, increasing lipid peroxidation, reducing antioxidants, and causing cell cycle arrest in AGS cells.…”
Section: Effect Of Zno Nps On Tumor Cell Model In Vitromentioning
confidence: 99%
“…In our research, we have demonstrated the application of ZnO NPs on bacteria (Figure 1A) and viruses (Figure 1B). 55 Numerous studies have reported the beneficial use of ZnO NPs in cancer treatment. For instance, it has been found that black mulberry loaded MN-ZnO NPs induce apoptosis in gastric cancer cells (AGS) by enhancing the formation of ROS, reducing mitochondrial membrane potential (MMP), evaluating apoptotic morphological changes using AO/EtBr, increasing lipid peroxidation, reducing antioxidants, and causing cell cycle arrest in AGS cells.…”
Section: Effect Of Zno Nps On Tumor Cell Model In Vitromentioning
confidence: 99%
“…The current study is a continuation of our research program aimed at developing antibacterial polymer-metal composites [49][50][51][52][53][54] and is focused on the PLA-Zn composites made from a matrix with hemostatic properties [35][36][37][38][39][40] (but without an inherent antibacterial effect [55]) and with an antipathogenic (antibacterial [56][57][58][59][60][61][62][63][64][65]; antiviral [66][67][68][69][70][71][72][73][74][75][76][77]; and antifungal [78][79][80][81][82][83][84][85][86][87]), hemostatic [88][89][90]…”
Section: Introductionmentioning
confidence: 99%
“…Bruera et al [ 27 ] immobilized laccase on nanoporous alumina for black liquor treatment; they found that immobilized laccase exhibited better pH stability and removal efficiency than free laccase. Because of their excellent biocompatibility, chemical stability, and non-toxicity, ZnO nanomaterials have been widely used as chemical sensors and antibacterial agents, as well as for environmental applications [ 28 , 29 , 30 ]. Jantiya Isanapong et al [ 31 ] evaluated the efficiency of immobilized laccase for the degradation of tertiary butyl alcohol (TBA) on ZnO nanostructures; they found that immobilized laccase exhibited better stability and degradation.…”
Section: Introductionmentioning
confidence: 99%